Fundamental of Entrepreneurship ENT300: SinggahSitok/ Rahmatullah Affandy... [et al.] - Affandy, Rahmatullah; Zuhaimi, Muhd Firkhan; Zulkifli, Zulhairi; Hadi, Acellia Ulanda; Joseph, Jenny (2013)
The name of the company is SinggahSitok. The form of the business is partnership which consists of five members. Each manager will contribute certain amount of capital stated in the agreement. The business offers a various flavours of milkshake which is Oreo, Milo and Apong sugar. All managers have the rights to participate in the management of the business. Rahmatullah bin Affandy as the General Manager, MuhdFirkhan bin Zuhaimi the marketing manager, Jenny Anak Joseph the Administration Manager , Zulhairi bin Zulkifli the Operation Manager and AcelliaUlandaBintiHadi as the Financial Manager. The selection of General Manager is based on agreement among the members selected based on skills and ability. The management of the business will be lead and assist by all four managers. The General Manager is responsible for planning, leading, controlling and organizing business. The Marketing Manager is responsible to market our business to the customers. Next, the Administration Manager responsible for the job that is related to administration such as planning and arranging the remuneration schedule of salary and wages. The Operational Manager is responsible to the entire job that is related to the operation and will supervise and coordinate the operation of the business. Last but not least, the Financial Manager will handle the financial matters such as preparing the budget and financial statement for expenses of each departments and control the flow of the money of the organization.